Guinea : Staff-Monitored Program. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Guinea is emerging from a prolonged period of political crisis. The new government has taken bold steps to address the serious macroeconomic imbalances. The intention to establish a special fund to govern spending from the recent windfall from the mining sector is commended by Executive Directors. The tightening of monetary policy will help drain the excess liquidity out of the economy. Guinea's foreign exchange market remains fragmented and underdeveloped. Revision of the mining code is important for establishing a better investment environment and improving governance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet